2015
DOI: 10.1103/physrevlett.114.206603
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Spin-Dependent Molecule-Ferromagnet Hybridized States Anisotropy in Cobalt Phthalocyanine Based Magnetic Tunnel Junctions

Abstract: Organic or molecular spintronics is a rising field of research at the frontier between condensed matter physics and chemistry. It aims to mix spin physics and the richness of chemistry towards designing new properties for spin electronics devices through engineering at the molecular scale. Beyond the expectation of a long spin lifetime, molecules can be also used to tailor the spin polarization of the injected current through the spin-dependent hybridization between molecules and ferromagnetic electrodes. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 38 publications
(52 reference statements)
4
48
0
Order By: Relevance
“…Using the above mentioned bulk parameters, from the measured frequency variation δF ≈ 0.5 GHz, we obtain a variation of the anisotropy field δH K ≈ 0.048 T corresponding to a variation of the anisotropy constant δK ≈ 51 kJ/m 3 . Our results are consistent with the studies reporting that organic molecules affect the surface magnetic properties mainly through interfacial effects [2,5,6,[10][11][12][13].…”
Section: B 1-(2-bisthienyl) Benzene (Btb) Measurementssupporting
confidence: 93%
See 2 more Smart Citations
“…Using the above mentioned bulk parameters, from the measured frequency variation δF ≈ 0.5 GHz, we obtain a variation of the anisotropy field δH K ≈ 0.048 T corresponding to a variation of the anisotropy constant δK ≈ 51 kJ/m 3 . Our results are consistent with the studies reporting that organic molecules affect the surface magnetic properties mainly through interfacial effects [2,5,6,[10][11][12][13].…”
Section: B 1-(2-bisthienyl) Benzene (Btb) Measurementssupporting
confidence: 93%
“…Moreover, this spin polarization depends on how strongly the molecules are linked to the surface. For instance, a spin polarization reversal due to the differing hybridization between Co-phthalocyanine molecules and each cobalt electrode has been evidenced in Co/CoPc/Co magnetic tunnel junctions [13]. Interface coupling was also found to strongly influence spin injection as demonstrated in the case of (La,Sr)MnO 3 /Alq 3 /Co magnetic tunnel junctions [1], or to stabilize an antiferromagnetic ordering at room temperature at the interface between a cobalt ferromagnetic layer and a paramagnetic organic manganese phthalocyanine (MnPc) layer [12].…”
Section: B 1-(2-bisthienyl) Benzene (Btb) Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier experimental studies have shown that the spins in ferromagnetic nanoparticles can interact with nearby orbital fields in organic molecules, generating spin–orbital interactions at the ferromagnetic/organic interface . Furthermore, using the ferromagnetic surface represents the most direct approach to inject spins into semiconductors, leading to a spin‐selective interface . In general, the spin‐selective interface requires the direct contact between a ferromagnet and an organic semiconductor by overlapping their orbital wave functions.…”
mentioning
confidence: 99%
“…Note that a recent study of spin-transport devices incorporating CoPc layers also shows the importance of ferromagnet/molecular orbital hybridization, e.g. giving rise to the new additional feature of large range control of the coercive field by the electric field [111].…”
Section: Spin Dependent Effects At Hybrid Interfacesmentioning
confidence: 99%